Inhibition of Neisseria gonorrhoeae by Lactobacillus Species That Are Commonly Isolated from the Female Genital Tract - St. Amant, Diane C. (American Society for Microbiology, 2002)
Epidemiological studies suggest H(2)O(2)-producing lactobacilli protect women against gonorrhea. Here we demonstrate that Lactobacillus crispatus and Lactobacillus jensenii, the most common lactobacilli in the female genital tract, inhibit gonococci in both acidic and neutral pH conditions. Inhibition was neutralized by bovine catalase, suggesting that H(2)O(2) is the primary mediator of inhibition.